Medial patellofemoral ligament fixation with suture tape augmentation decreases lateral patellar motion without changing contact pressure - Nima Rezaie; Wesley R. Stroud; David P. Beason; Jonathan S. Slowik; Travis Dias; Grant M. Uldrich; Glenn S. Fleisig; Jeffrey R. Dugas (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose Medial patellofemoral ligament (MPFL) reconstruction has been the standard of care for recurrent patellar dislocations and chronic patellar instability. MPFL repair has been used as an alternative surgical option. The purpose of this study was to assess patellar stability and patellofemoral contact mechanics following MPFL fixation with suture tape augmentation. We hypothesized that lateral patellar motion would be reduced. Methods In twelve cadaver knees, a hole was drilled near the midpoint of the medial patella. Three locations were drilled on the femur Schöttle's point, 1 cm anterior to Schöttle's point and 1 cm proximal to Schöttle's point. Each knee was then held at 30° of knee flexion, and the patella was subjected to a physiologic lateral force. The resulting motion was measured, and patellofemoral contact forces were recorded. This process was performed with the MPFL torn and then bolstered with suture tape augmentation anchored centrally in the medial patella and each of the three femur hole locations. Results All MPFL augmentations provided significantly less lateral patellar motion compared to the torn condition. Contact area was significantly greater in the augmented condition than in the torn condition, but no statistical differences were observed in patellofemoral contact pressure. No significant differences in lateral patellar motion, contact pressure or contact area were found between femoral anchor positions. Conclusions MPFL fixation with suture tape augmentation significantly decreased lateral patellar motion compared to the torn condition without causing significant changes in contact pressures within the patellofemoral joint. Level of Evidence N/A.